Post choice satisfaction among Nigerian students studying in Malaysian universities: A pilot study - Biodun, Aliyu Bukola (Macrothink Institute, 2012)
Purpose – This research aims at developing a conceptual framework and valid prepositions of the impacts of Nigerian students’ perceived expectation on perceived quality and satisfaction with Malaysian higher institutions.The result of this study will be used for a further research that will empirically establish the actual reason for the increasing influx of Nigerian students in Malaysia and how the stakeholders can best explore the inherent opportunities. Design/methodology/approach – The researchers primarily use qualitative approach and pilot study that involves detail literature reviews of academic literatures and industry reports on perceived expectation, perceived quality and student satisfaction.Findings – The extant literatures suggest that there exist positive relationship between perceived expectation, perceived quality and student satisfaction. The reliabilities of the proposed measurement instruments indicate valid internal consistency. Research limitations/implications – Given that this paper is based on qualitative approach, there is need to embark on empirical data gathering to validate the conceptual model. Practical implications – Evidence from existing literatures have established that for higher institutions of learning to achieve operational efficiency in their perceived service quality and student satisfaction, managements of higher institutions need to integrate high quality lecturers, reasonable cost of education, social orientation programs, modern facilities etc into their operations’ measurement practices. Originality/value – This research extensively review existing literatures on student satisfaction and measurements, specifically how it impact education industry.It primarily avails both the academic and higher institution’s management the benefits that are inherent in measuring the impact of perceived expectation on perceived quality and student satisfaction.The research finally proposed a model for future empirical testing.